Exploring the Potential of Posidonia oceanica Fibers in Eco-Friendly Composite Materials: A Review - Cristiano Fragassa; Ana Pesic; Sara Mattiello; Ana Pavlovic; Carlo Santulli (Journal of Marine Science and Engineering)
The growing demand for sustainable materials has driven the exploration of natural fibers as eco-friendly alternatives to synthetic reinforcements for composites. This study investigates the potential of Posidonia oceanica, an abundant marine biomass, which is often driven to be stacked on the backshore and used so far for energy recovery and low-value applications, as a filler and possible reinforcement in cementitious and polymer composites. Most applications of Posidonia are concentrated in the Mediterranean area and focused on the construction industry. However, its introduction in polymer composites, especially as a source of cellulose or in combination with the use of bio-based matrices, can also be proposed. With this aim, the physical and chemical properties of Posidonia oceanica fibers need to be characterized, and their compatibility with various matrices needs to be evaluated. Experimental results demonstrate that Posidonia oceanica fibers, especially when treated with alkali and silane, or combining both treatments, can exhibit mechanical properties quite comparable to other natural fibers, namely to those obtained from grass species. As with any other type of waste, yet with more interest for its wide accumulation over the coastal line, the use of Posidonia oceanica in composites may contribute to reducing the environmental footprint of these materials, aligning with circular economy principles. This review highlights the dual benefits of utilizing marine biomass by advancing material sustainability while not being detrimental to coastal waste management.